Carrier-envelope phase stabilization by controlling compressor grating separation - Li, Chengquan; Mashiko, Hiroki; Wang, He; Moon, Eric; Gilbertson, Steve; Chang, Zenghu (My University, 2008)
Previously, we demonstrated the stabilization of the carrier-envelope (CE) phase of the laser pulses from a chirped pulse amplifier by controlling the effective grating separation in the stretcher. In this work, we show that the CE phase can also be stabilized to ∼230mrad by controlling the grating separation in a compressor. The cutoff frequency of the piezoelectric transducer mounted grating for the phase stabilization system was found to be higher than 60Hz.